Tourist perceptions and attitudes regarding the impacts of climate change on Victoria Falls - Dube Kaitano; Nhamo Godwell (Bulletin of Geography. Socio-Economic Series, 2020)
Tourist perceptions are critical in shaping tourism development at a destination. Regardless of the centrality and vulnerability of the tourism industry, tourism geographers have been shying away from perception studies, and more so in Africa. Some of the destinations most vulnerable to climate change and related weather activities are water-based natural resorts. Recent droughts have ignited an intense debate that has brought the future viability of tourism in Victoria Falls into question. Using a mixed-method approach, the study sought to document tourist perceptions and attitudes regarding the impact and future of the Victoria Falls World Heritage Site. It emerged that Victoria Falls is categorised as a last-chance tourism destination. Going forward there is need for continuous resort monitoring, tourism product diversification, and transparency and proper communication, particularly during years of extreme droughts, in order to avoid tourism disruption. Climate change action is a must for all tourism stakeholders to save the resort.